PREVALENCE OF ASYMPTOMATIC URINARY TRACT INFECTION IN PREGNANT AND NONPREGNANT WOMEN IN A TERTIARY CARE TEACHING HOSPITAL - LAXMI, RAJAMANICKAM VENKATA; PIDUGU, SAILAJA; SREE, ALLAVARAPU RAMYA (International Journal of Current Pharmaceutical Research, 2023)
Objective: The study's main objective was to isolate and characterize the bacteria that cause asymptomatic UTIs in pregnant and nonpregnant women attending a tertiary care teaching hospital. Methods: It is a comparative cross-sectional study that was carried out from January 2021 to January 2022. A structured questionnaire was used to gather clinical information (such as parity and the history of UTIs) and sociodemographic data (such as age, marital status, educational level, place of residence, occupation, and income) from eligible participants. A total of 200 urine samples were collected (100 pregnant and 100 nonpregnant) and analyzed using standard microbiological methods for the detection of isolates and their antibiotic sensitivity using the Kirby-Bauer method. Results: Most patients who participated were aged 21-30 y (50.5%). E. coli incidence was more in UTI of pregnant women (42.3%) and nonpregnant women (34.2%). Among the 33 isolates of E. coli from pregnant and nonpregnant women, most strains were resistant to amoxicillin+clavulanic acid (57.6%) and cotrimoxazole (54.5%). They were sensitive to other tested antibiotics like norfloxacin, nitrofurantoin, gentamicin, and cefuroxime. Conclusion: Pregnant women were more likely to get UTIs than nonpregnant women, and the frequency of UTIs among women was more significant. It is recommended that women, especially pregnant women, undergo routine UTI screenings to identify infected cases and receive prompt treatment to prevent urinary problems.